Description of four new synallactid species (Holothuroidea, Synallactida, Synallactidae) from the tropical Western Pacific Ocean - Yunlu Xiao; Ning Xiao (ZooKeys)
Four synallactid specimens were collected during four deep-water benthic fauna surveys (2013–2018) conducted at three seamounts (‘Jiaolong’, ‘Y3’, and ‘M4’) and the Ganquan Plateau in the South China Sea, tropical Western Pacific Ocean, at depths ranging from 344 to 3610 m. Morphological examination of these specimens revealed four new species belonging to three genera, which are described as Synallactes tenuibrachius sp. nov., Bathyplotes liaoi sp. nov., Bathyplotes varicolumna sp. nov., and Amphigymnas ganquani sp. nov. Notably, Amphigymnas ganquani sp. nov. represents the first report of an Amphigymnas species in the South China Sea. Detailed descriptions are provided for the morphological features, including the type locality, and geographic and bathymetric distributions of these species. These findings contribute to the understanding of seamount biodiversity and provide valuable insights for advancing research on seamount ecology, management, and conservation.